(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Now a days, solar energy has become a prominent renewable energy resource. With solar tracking, it will become possible to generate more energy since the solar panel can maintain a perpendicular profile to the rays of the sun. Even though the initial cost of setting up the tracking system is considerably high, there are cheaper options that have been proposed over time. This paper presents the design and construction of a prototype for solar tracking system that has a dual axis of freedom. Light Dependent Resistors (LDRs) are used for sunlight detection. This paper focuses on the new approach development which controls the solar panel movement. The objective of this paper is to implement& simulate the controlalgorithm which is most suitable and efficient on the solar tracker dual-axis which can rotate in directions of both azimuth and elevation. This paper mainly aims the solar energy optimization harnessing with solar panels sun tracking dual axis using LDR.